PERBAIKAN PARESIS SARAF KRANIAL III IV V DAN VI BERDASARKAN PEMERIKSAAN NEUROLOGI KLINIS PADA KARSINOMA NASOFARING PASCATERAPI - Linda Suryakusuma,* Eva Dewati,* Sri Mutya Sekarutami,** Joedo Prihartono,*** Tiara Aninditha* (NEURONA, 2016)
INTRODUCTION NASOPHARYNGEAL CANCER NPC IS THE MOST PREVALENT HEAD AND NECK CANCER IN INDONESIA THIRD FOURTH FIFTH AND SIXTH CRANIAL NERVES PALSY ARE OFTEN FOUND IN NPC AND SIGNIFY INTRACRANIAL INFILTRATION CLINICAL NEUROLOGICAL EXAMINATION FOR CRANIAL NERVES IS ONE METHOD OF EVALUATING NPC PATIENTS AFTER RECEIVING STANDARD MANAGEMENT